150 minutes of vigorous physical activity per week predicts survival and successful ageing: a population-based 11-year longitudinal study of 12 201 older Australian men. Issue 3 (3rd September 2013) - Almeida, Osvaldo P; Khan, Karim M; Hankey, Graeme J; Yeap, Bu B; Golledge, Jonathan; Flicker, Leon
Abstract : Background: Physical activity has been associated with improved survival, but it is unclear whether this increase in longevity is accompanied by preserved mental and physical functioning, also known as healthy ageing. We designed this study to determine whether physical activity is associated with healthy ageing in later life. Methods: We recruited a community-representative sample of 12 201 men aged 65–83 years and followed them for 10–13 years. We assessed physical activity at the beginning and the end of the follow-up period. Participants who reported 150 min or more of vigorous physical activity per week were considered physically active. We monitored survival during the follow-up period and, at study exit, assessed the mood, cognition and functional status of survivors. Healthy ageing was defined as being alive at the end of follow-up and having a Patient Health Questionnaire score <10, Telephone Interview for Cognitive Status score >27, and no major difficulty in any instrumental or basic activity of daily living. Cox regression and general linear models were used to estimate HR of death and risk ratio (RR) of healthy ageing. Analyses were adjusted for age, education, marital status, smoking, body mass index and history of hypertension, diabetes, coronary heart disease and stroke. Results: Two thousand and fifty-eight (16.9%) participants were physically active at study entry. Active men had lower HR of death over 10–13 years than physically inactive men (HR=0.74, 95% CI=0.68 to 0.81). Among survivors, completion of the follow-up assessment was higher in the physically active than inactive group (risk ratio, RR=1.18, 95% CI=1.08 to 1.30). Physically active men had greater chance of fulfilling criteria for healthy ageing than inactive men (RR=1.35, 95% CI=1.19 to 1.53). Men who were physically active at the baseline and follow-up assessments had the highest chance of healthy ageing compared with inactive men (RR=1.59, 95% CI=1.36 to 1.86). Conclusions: Sustained physical activity is associated with improved survival and healthy ageing in older men. Vigorous physical activity seems to promote healthy ageing and should be encouraged when safe and feasible.